Analisis Stabilisasi Tanah Dasar dengan Cerucuk Bambu dan Geotekstil - Muhammad Naufal Luthfiyyah; Hadi Kusumah; Hartono (Department of Civil Engineering, Faculty of Engineering, Universitas Brawijaya, 2023)
The road plays an essential role as a driving force for development growth in Sukabumi. The access section is an organic clay type with low bearing capacity, so it needs subgrade stabilization. The DCP test obtained a value of 0.76%. The carrying capacity value is in a poor classification. Therefore, it is necessary to strengthen the soil layer using bamboo culms and geotextiles. After that, it is required to do a field CBR. After supporting bamboo culms, the carrying capacity value is 5.63%. This value meets the CBR requirements in medium classification. Thus, it is necessary to add a pavement layer with geotextile. This bearing capacity test obtained a value of 20.59% and is in excellent classification.